Socio-demographic Factors Associated with Loss to Follow up Anti Retro Viral Therapy among People Living with HIV and AIDS in Semarang City - Sutini, Sutini; Hary Cahyati, Widya; Ratna Rahayu, Sri (Universitas Negeri Semarang, 2020)
Longlife Anti Retro Viral (ARV) treatment is an important component of Human Immunodeficiency Virus (HIV) care. Loss to follow up (LTFU) defined as not taking ARV refill for 3 months or longer from the last attendance for refill and not yet classified as dead or transferred out, this causes morbidity and mortality related to Acquired Immune Deficiency Syndrome (AIDS). The incidence of LTFU in ARV therapy among people living with HIV and AIDS (PLWHA) in Semarang City 924 people (21%) (WHO target LTFU <20%). The aim of this research is to analyze education level, employment status and distance from residence to health services that affecting loss to follow-up of ARV therapy among people living with HIV and AIDS in Semarang City. The research used case control design. The sample of the research was 134 (67 cases and 67 controls) respondents obtained by purposive sampling technique. Technique for collecting the data were interview and questionnaire. Chi square and logistics regression test were used in analyzing the data. The result of the research showed that there were significant influences in the variables of education (p = 000), employment status (p = 0,000), distance from home to health services (p = 0.009 affect loss to follow up of antiretro viral therapy among people living with HIV and AIDS in Semarang City. Multivariate models showed the most influential factors was education level (p= 0,000. OR = 6.270). A treatment literacy program should be emphasized to people living with HIV and AIDS who are starting treatment and during treatment ARV.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â